2010
DOI: 10.1002/car.1127
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and ecological contexts of violent punishment and restraint of Negev Bedouin children: from understandings to interventions

Abstract: Over recent decades we have become increasingly sensitised to the importance of considering the cultural and ecological contexts of child abuse. This paper illustrates the necessity for but also the complexity of doing so in practice, through refl ection on some of the dilemmas faced by social work professionals encountering physical punishment and restraint of children among the Negev Bedouin. We describe several cases and refl ect on two central challenges. First, we point to a signifi cant grey area remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Given the careful, cautious and complex negotiations needed to gain the best outcomes for children without causing public shame, it was felt important that child protection workers were also community members, ensuring that they have intimate understanding of the communities that they work in. Garb and Goren () also found that careful readings of the complex interplay between cultural and contextual factors were required when working with Negev Bedouin families and their children in Islamic contexts. Literature has shown that it is very difficult to perceive the world of another and easy to impose our views on others even while trying to be culturally sensitive (Connolly et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the careful, cautious and complex negotiations needed to gain the best outcomes for children without causing public shame, it was felt important that child protection workers were also community members, ensuring that they have intimate understanding of the communities that they work in. Garb and Goren () also found that careful readings of the complex interplay between cultural and contextual factors were required when working with Negev Bedouin families and their children in Islamic contexts. Literature has shown that it is very difficult to perceive the world of another and easy to impose our views on others even while trying to be culturally sensitive (Connolly et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the wealth of literature on the rights and obligations of parents and their children under Islam, and the importance of promoting partnerships between INGOs and faith communities (Robinson, ; UNICEF, ), there is a lack of literature and little discussion on the practical application of these principles (Garb and Goren, ). This includes their conversion into child protection programmes and the role of non‐Islamic parties in promoting these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable paper from Israel (Garb and Goren, 2010) explores the challenge of intervening in the lives of Bedouin children who live in a society that is radically disadvantaged and whose traditional way of life is threatened and restricted by the State. Illustrated by vivid case examples, the paper explores some of the cultural values and structural constraints that force communities, families and individuals into using damaging practices including violent discipline and restraint.…”
mentioning
confidence: 99%